The emerging global framework for the governance of large-scale land-based investment: A literature review - Nanna Lynggard; Helle Munk Ravnborg (Danish Institute for International Studies (DIIS), 2020)
A new global framework for governing large-scale land-based investments is in the making. By being voluntary and with the Voluntary Guidelines for the Governance of Tenure (VGGT) as the most well-known example of this new generation of rights-based governance instruments, many observers agree that these instruments represent a new regulatory approach. While considered a weakness by many, the literature reviewed in this DIIS Working Paper suggests that this very feature of being voluntary may turn out to be a strength of the emerging governance framework in addressing land-based agricultural investments. By influencing public debates over large-scale land-based agricultural investments and thus affecting normative standards, it seems that global and UN anchored frameworks such as the VGGT and the UN Guiding Principles of Business and Human Rights as well as private initiatives such as the Roundtable of Sustainable Biofuels are gradually being incorporated into harder law and regulatory frameworks. In this way, soft law may have an impact on policy development and practice precisely because of its lack of immediate legal effect, as well as by exercising an informally 'soft' but nonetheless strong normative influence.
Keywords: 330; Water governance; Food and agriculture; Land rights and investments; Inequality and poverty; Development in practice; World politics; Global economic governance; Emerging economies; Conflict and economy